Pengaruh Komitmen Anggaran dan Kultur Organisasional terhadap Hubungan Partisipasi Penganggaran dan Kinerja Manajerial pada Kondisi Stretch Targets - Titien Damayanti (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2007)
This purpose of this research is to test the effect of budget commitment and organizational culture to relationship budgeting participation and managerial performance at stretch targets condition. This research uses 131 all departmental managers of three to five-star hotel in Java and Bali and the method of data collection is purposive method and uses variable measurement of the Likert scale. The hypothesis is tested by path analysis of structural equation modeling. The research shows that budget commitment and organizational culture have significantly affect to relationship budgeting participation and managerial performance at stretch targets condition in which budget commitment partially mediate and organization culture job-oriented moderated by negatively significant on the increasing manager performance.Keywords: Budgeting participation, budget commitment, organizational culture, managerial performance, stretch targets.